Determinants of Bond Rating, Profitability, Liquidity, and Company Size are Moderated Leverage on the Yield to Maturity - Sihombing, Pardomuan; Bonowati, Yosephine Amanda; Zakchona, Elia (Jurnal Manajemen Indonesia, 2024)
This study aims to identify the determinants of yield to maturity of corporate bonds in Indonesia with leverage as a moderating variable. The data for this study is 25 corporate bonds as a sample from a total population of 59 corporate bonds. The research sample was tested using panel data analysis techniques, namely descriptive and inferential statistics. The test results show that profitability with the Yield of Assets indicator and company size has a positive effect, liquidity with the Current Ratio indicator has a negative effect and bond ratings do not affect the yield to maturity of corporate bonds in Indonesia. Furthermore, it was found that there is a role of leverage as a moderating variable, namely, leverage weakens the effect of ROA and bond ratings on the yield to maturity of corporate bonds and strengthens the effect of the Current Ratio on the yield to maturity of corporate bonds.